The characterization of hematopoietic tissue in adult Chinese mitten crab Eriocheir sinensis. (July 2016) - Jia, Zhihao; Kavungal, Sharath; Jiang, Shuai; Zhao, Depeng; Sun, Mingzhe; Wang, Lingling; Song, Linsheng
Abstract: Invertebrates rely on the efficient innate immune mechanisms against invaders, in which the continuous production of hemocytes (hematopoiesis) is indispensable. In the present study, the hematopoietic tissue (HPT) from Chinese mitten crab Eriocheir sinensis was identified and characterized. It was a thin and non-transparent sheet located at the dorsolateral side of the stomach, which was composed of a series of ovoid lobules. Each lobule was surrounded by connective tissue containing a large amount of spherical cells with big nucleus. In HPT, the cells were full of mitochondria and granules, and DNA replication was detected in some cells by EdU labeling technique. Cell proliferation was observed in HPT by transmission electron microscope (TEM). The distribution of two transcription factors, GATA1 and RUNX1, were examined by human GATA1 and RUNX1 antibodies, respectively. Three homologues of RUNX1 were detected in the HPT while no signal of RUNX1 was observed in hemocytes, and GATA1 was detected in both HPT and some hemocytes. The mRNA transcript of a novel hematopoiesis related cytokine Es Ast was detected in hepatopancreas and hemocytes, but it was no detectable in HPT. The mRNA expression level of Es Ast in hepatopancreas was 1.38-fold higher than that in hemocytes. Total hemocytes counts were related to the mRNA expression level of Es Ast post Aeromonas hydrophila challenge. The results suggested that the stem cells in the hematopoietic tissue of Chinese mitten crab E. sinensis were regulated by transcriptional and humoral factors to generate hemocytes. Highlights: The hematopoietic tissue from Chinese mitten crab Eriocheir sinensis was isolated from the dorsolateral side of the stomach. Stem cells were identified in Es HPT. GATA1 and RUNX1 were expressed in Es HPT. A novel crustacean cytokine Es Ast was not expressed in Es HPT.